Defense Mechanism Of John Brennan In Paul Haggis's The Next Three Days Movie (2010): A Psychoanalytic Approach - Rayuni, Feni Dhian Cheri (2012)
This study is aimed to show the defense mechanism that the major character has by using psychoanalytic approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the seconds is analyzing the movie based on the psychological analysis. This research is qualitative research; type of data of the study is text and image taken from two data sources; primary and secondary. The primary data source is The Next Three Days movie directed by Paul Haggis released in 2010. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. Firstly, based on the structural analysis, it is clear that in this movie, Paul Haggis conveys a message that people have defense mechanism on them to protect them from danger. Secondly, based on the psychoanalytic analysis, it is evident that in this movie, Paul Haggis expresses the psychoanalytic phenomena that each person has a defense mechanism.